TORREFICATION OF DIPTEROCARP WOOD BY BRICK BEEHIVE KILN - Kiatgrajai, Preecha; Puthsorn, Pratuang; B. Iantican, Celso (วารสารวนศาสตร์ไทย, 2022)
About 26 cu m of dipterocarp wood from sawmill wastes were carbonized in a 2 cu m brick beehive kiln. 14 kilns representing 7 experiments were tested at maximum temperature (400 to 700 ° C). Charcoal and torrefied wood yield ranged from 45-52% when temperature was lower than 400° C but only about 30% when the temperature was greater than 600° C. Charcoal produced at low temperature had poor heat of combustion, volatile matter content, fixed carbon content and heat utilization efficiency, but had good properties for the ferrocement gasifier. Torrefied wood and raw wood are not appropriate to use with a ferrocement gasifier. Torrefied wood is difficult to reduce to proper size for use with a charcoal bucket stove